PENGEMBALIAN INVESTASI PADA PT PAULA JAYA DI SAMARINDA - Elfreda Aplonia Lau 3, Melida Frensiska P, Robin Jonathan2, (EKONOMIA, 2015)
The purpose of this study was to determine maximum limit of return heavy equipment in the form of Excavator brand Caterpillar 320D and Dump Truck brand Hino 130HD in PT. Paula Jaya Samarinda. The analysis tools being used was Payback Period, by examining operating cost, investment cost, and depreciation costs heavy equipment Excavator brand Caterpillar 320D and Dump Truck brand Hino 130HD in PT. Paula Jaya Samarinda followed by a search for the value of proceed/Net Cash Flow. Based on the results of a study the return of investment Excavator Caterpillar 320D for 4 years and 3 months and Dump Truck Hino 130HD for 4 years and 5 months, from the results payback period is shorter than the economic life and management estimates about the maximum return on investment during 7 years calculated from the purchase of heavy equipment in 2011.